Platelet-Rich Fibrin in the Closure of Tympanic Membrane Perforations: A Narrative Review - Rika Intania Rahma Pratiwi (UMSU, 2026)
Abstract: Tympanic membrane perforation, caused by trauma, iatrogenic factors, or infection, affects 1-4% of the global population and may lead to permanent hearing loss. Conservative management shows variable failure rates, while conventional surgical approaches like myringoplasty and tympanoplasty are invasive, time-consuming, expensive, and associated with complications. Platelet-Rich Fibrin (PRF) emerges as a promising autologous biomaterial alternative. This narrative review comprehensively evaluates PRF's clinical efficacy, mechanisms of action, safety profile, and limitations in managing tympanic membrane perforations. A systematic search was conducted across Google Scholar, PubMed, and ScienceDirect databases using relevant keywords. Inclusion criteria encompassed original research articles including clinical trials, cohorts, and case series discussing PRF application in tympanic membrane closure. Reviews, meta-analyses, editorials, and single case reports were excluded. Results demonstrate PRF achieves 92% success rates with an average 8-day healing time, surpassing conventional treatments. PRF functions as a biological scaffold providing growth factors for tissue regeneration. Safety profile is favorable with mild complications including granulation (7.69%) and otomycosis (1.6-19.23%). However, success rates decrease to approximately 80.76% in large perforations, emphasizing proper patient selection. PRF represents an effective and safe adjuvant therapy for tympanic membrane perforation management with minimal adverse effects.